Sports Training Principles - Dick, F. W. (Bloomsbury Publishing Plc, 2014)
This is the new, fully revised, sixth edition of this ultimate reference tool for all coaches responsible for training athletes to fulfill their performance potential. Written by world-renowned and highly sought after coach and President of the European Athletics Coaches Association, Frank W. Dick, with contributions from Professor Timothy Noakes (University of Cape Town, South Africa), Dr Penny Werthner (University of Calgary, Canada), Scott Drawer (Athletic Performance Manager of Rugby Football Union), Vern Gambetta (USA Track & Field), Dr Cliff Mallett and Dr David Jenkins (University of Queensland, Australia), this textbook comprehensively covers the core aspects of sports coaching which can be applied to all sports and disciplines. This new edition has been extensively revised to incorporate the latest theory and practice in sports training and coaching, with supplementary contributions from international experts. The book covers the key sports science topics: Anatomy and physiology; Biomechanics, Psychology; Nutrition; Performance Analysis; Training; and Coaching methods. This is a highly recommended resource for students of applied sports science, sports coaching, sports development, PE teachers, fitness advisers, coaches and athletes. (Text: Bloomsbury)